Recent advances in understanding antitumor immunity [version 1; referees: 3 approved] - Rodrigo Ramella Munhoz; Michael Andrew Postow (F1000Research, 2016)
The term “antitumor immunity” refers to innate and adaptive immune responses which lead to tumor control. Turning the immune system into a destructive force against tumors has been achieved in a broad range of human cancers with the use of non-specific immunotherapies, vaccines, adoptive-cell therapy, and, more recently with significant success, through blockade of immune checkpoints. Nevertheless, the efficacy of these approaches is not universal, and tools to identify long-term responders and primarily refractory patients are warranted. In this article, we review recent advances in understanding the complex mechanisms of antitumor immunity and how these developments can be used to address open questions in a setting of growing clinical indications for the use of immunotherapy.